Do or Die: The Dilemma of Higher Education in South Sudan - Kuany, David Malual W. (International Higher Education, 2016)
South Sudan, the world’s newest nation, faces severe problems in developing it’s higher education institutions due to civil war, poverty, and other factors. Yet, universities are growing. This article discusses the challenges and accomplishments.